ANALISIS RETURN ON INVESTMENT (ROI), RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Farah Adiba; Dhinik Saputri (STIA MALANG, 2023)
Currently, stock investment has increased significantly because it provides promising profits, but not a few alsoexperience failure when investing in shares. So before deciding to invest in shares, potential investors mustanalyze the finances of a company by looking at several financial ratios, including ROI, ROE and EPS. Thisstudy has a formulation of the problem whether the variables ROI, ROE and EPS affect stock prices and whichof these variables most affect stock prices. While the purpose of this study is to examine the effect of ROI, ROEand EPS on Stock Prices both partially and simultaneously. The research method used in this study isExplanatory Research with a sample of 10 banking companies listed on the Indonesia Stock Exchange (IDX).The data used is secondary data collected using the data documentation method. Data analysis techniques usemultiple linear regression analysis. The theoretical basis used is the theory of ROI, ROE, EPS and Stock Price.Based on the data analysis conducted, data was obtained that ROI partially has no effect on stock prices, ROIpartially has no effect on stock prices, EPS partially affects stock prices and together ROI, ROE and EPS affectstock prices. As well as the EPS variable that most dominantly affects stock prices.